The Romans - Barrow, R. H. (Harmondsworth : Pinguin Books, 1972)
Kings, republic, empire - From city-state tot republic - The restoration and the Augustan Principate - Vergil - Horace - The roman practical gemius, attitude to religion and philosophy - The age of crisis and rescue - Diocletian - Constantine - Christianity - The roman law